(untitled) (Journal of the College of Basic Education, 2022)
Today’s interest in e-learning has become utmost but the responsibilities of the parameter and non-educational teacher can affect the progress of the e-learning process. Defense of interest in alternative e-learning about the teacher through the presence of an electronic teacher can be useful at the moment to fill a lot of needs for this and this can be represented by the problem of the current research in question: What are teachers and school teachers. The aim of researching: The electronic teacher proposal for educational tasks to activate contemporary learning from the point of view of teachers and secondary school teachers. The teams of teachers and teachers of practitioners for electronic education in the city of Karbala (the city center and limbs) in the Karbala Education Directorate. For school year (2022-2021). The researcher used the descriptive research approach. The current research community included teachers and teachers by class, a degree at 523 and a high degree (95). Distributors at the city center and limbs. After checking the standard characteristics of honesty indicators, stability and statistical analysis of the scale for the professionalism of the Egyptian teacher for reality functions of realization of 14 (14) paragraph (14) paragraph distributed on three components: an effective and discretionary regulatory regulatory cognitive, according to a three-way response is: [task, task Somewhat, is not important]. It is given when corrected grades and is given when corrected grades of a degree (1) minimum, and 3 grade. The highest value (42) and less value (14) in central each (28). Search to search to 1) There is a direction towards using the electronic teacher 2) There is a difference between teachers in orientation towards the proposal of an electronic teacher 3) There is a difference between scientific degree in orientation towards the proposal of an electronic teacher 4) There is no difference between geographical distribution in orientation towards the proposal of electronic teacher.